ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY (Studi Empiris pada Perusahaan LQ 45 yang terdaftar di Bursa Efek Indonesia Periode Tahun 2010-2013) - Anthusian Indra Kurniawan; Herry Laksito (Diponegoro Journal of Accounting, 2015)
This research aimed to analyze the size of company, profitability, solvability, type of industry, auditor's opinion, and the reputation of the Public Accounting Firm significantly affect audit delay in companies belonging LQ 45 in Indonesia Stock Exchange (IDX) in the period 2010-2013. Samples that have been determined and obtained as many as 174 sample. This research used secondary data from financial statement of the company's were classified LQ 45 in Indonesia Stock Exchange (IDX) in the period 2010-2013. Statistical methods used in this research is multiple linear regression at a significance level of 5%.Results from this study indicate the variable size of company, type of industry, auditor's opinion, and reputation of the Public Accounting Firm significantly influence audit delay variable. Profitability and Solvability factors showed no significant effect on audit delay.